Self-Compassion pada Dewasa Awal dengan Fatherless: Penelitian - Mutia Shafa Zukhulaika; Ratna Yunita Setiyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Fatherlessness is increasingly prevalent in Indonesia and has notable effects on emotional development, particularly during emerging adulthood. The absence of a father figure may hinder individuals’ ability to cultivate self-compassion. This study aims to explore the dynamics of self-compassion among emerging adults who experience fatherlessness. A qualitative case study approach was employed through in-depth interviews and observations with two emerging adult participants. Data were analyzed using Neff’s three components of self-compassion: self-kindness vs. self-judgment, common humanity vs. isolation, and mindfulness vs. over-identification. The findings show that both participants demonstrated low self-kindness and high self-judgment, reflected in excessive self-criticism and feelings of unworthiness. In the area of common humanity, participants tended to feel isolated and believed their suffering was unique. Regarding mindfulness, they recognized their emotions but often became overwhelmed by negative affect. This study concludes that fatherlessness significantly contributes to low self-compassion in emerging adults, particularly through patterns of self-criticism, emotional isolation, and difficulties in emotion regulation.